Asistensi Penyusunan SBI e-Pocketbook sebagai Alat Pengendalian Anggaran Berbasis Kinerja - Ahmad Abbas (Jurnal PkM Pengabdian kepada Masyarakat, 2022)
As one of the educational institutions under the Ministry of Religion Indonesia established in 2016, STAIN Majene is led to conduct the optimization of a performance-based budgetary control system through costing standards. This development activity was designed using Participatory Action Research (PAR).  The model of development of the product used 4D model (Define, Design, Development, and Dissemination) adopted from the model of Thiagarajan et al. (1974). Afterward, users of budgeting were taught so they were proficient at using the product of Internal Cost Standard (SBI).  The result of this activity discloses that the SBI book is successful to be produced in the form of a digital known as the SBI e-pocketbook to budgetary users in STAIN Majene.  It is a costing unit acting as the guidance of internally budgetary calculation of STAIN Majene and a necessary instrument in making budgetary allocations so that SBI product contributes to budgetary users in STAIN Majene.